The California Tobacco Control Program's effect on adult smokers: (2) Daily cigarette consumption levels. Issue 2 (30th March 2007) - Al-Delaimy, Wael K; Pierce, John P; Messer, Karen; White, Martha M; Trinidad, Dennis R; Gilpin, Elizabeth A
Abstract : Objective: To investigate the association of the California Comprehensive Tobacco Control Program with self-reported population trends of cigarette consumption during 1992–2002. Setting and Participants: Participants were non-Hispanic white daily smokers (aged 20–64 years, n = 24 317) from the Tobacco Use Supplements to the Current Population Survey (1992–2002). We compared age-specific trends in consumption among daily smokers in three groups of states with differing tobacco control initiatives: California (CA; high cigarette price/comprehensive programme), New York and New Jersey (high cigarette price/no comprehensive programme), and tobacco-growing states (TGS; low cigarette price/no comprehensive programme). Results: There was a general decline in cigarette consumption across all age groups in each category of states between 1992 and 2002, except the oldest age group in the TGS. The largest annual decline in the average number of cigarettes per day was observed among daily smokers in CA who were aged ⩾35 years (−0.41 cigarettes/day/year (95% CI −0.52 to −0.3)). This rate was significantly higher than the −0.22 cigarettes/day/year (95% CI −0.3 to −0.16; p<0.02) observed in same-age daily smokers from New York and New Jersey, and significantly higher than the rate in same-age daily smokers from the TGS (−0.15 cigarettes/day/year (95% CI −0.22 to −0.08; p<0.002)). There were no significant differences across state groups in the decline observed in daily smokers aged 20–34 years. In 2002, only 12% of daily smokers in CA smoked more than a pack per day, which was significantly lower than the 17% in New York and New Jersey, which again was significantly lower than the 25% in the TGS. Conclusions: The California Tobacco Control Program was associated with significant declines in cigarette consumption among daily smokers aged ⩾35 years of age, which in turn should lead to declines in tobacco-related health effects. The decline in consumption among young adult smokers was a national trend.